How to Build and Assess the Quality of Healthcare-Related Research Questions - Ubeda, Sergio Ramón Gutiérrez (Global journal on quality and safety in healthcare (Print), 2022)
The objective of this article is to describe a simplified process for building and assessing the quality of healthcare-related research questions. This process consisted of three stages. The first stage aimed to select and explore a field of science. This field would be the area for which to identify outputs, such as units of analysis, variables, and objectives. The second stage aimed to write structured research questions, taking into account the outputs of the first stage. In general, the structure of research questions starts with interrogative adverbs (e.g., what and when), auxiliary verbs (e.g., is there and are there), or other auxiliaries (e.g., do, does, and did); followed by nouns nominalized from verbs of research objectives, such as association, correlation, influence, causation, prediction, application; research variables (e.g., risk factors, efficiency, effectiveness, and safety); and units of analysis (e.g., patients with hypertension and general hospitals). The third stage aimed to assess the quality and feasibility of the research questions against a set of criteria such as relevance, originality, generalizability, measurability, communicability, availability of resources, and ethical issues. By following the proposed simplified process, novice researchers may learn how to write structured research questions of sound scientific value.